Salmonella Typyhi Isolated From Urine Culture before Percutaneous Nephrolithotomy: A Case Report - Degirmenci, Tansu; Ar?, Alpay; Kozacioglu, Zafer; Ors, Bumin; Gunlusoy, Bulent (Urology Journal, 2014)